Franse Affiches. (Arnhem : Gemeentemuseum, 1953)
Berard, Christian ; Bonnard, Pierre ; Boticelli, Sandro ; Braque, Georges ; Cheret, Jules, Clairin, Pierre ; Colin, Jean ; Daumier, Honoré ; Dubuffet, Jean ; Delacroix, Eugène ; Dufy, Raoul ; Giacometti, Alberto ; Leger, Fernand ; Laurens, Henri ; Maillol, Aristide ; Matisse, Henri ; etc.
Franse Affiches, Gemeentemuseum, Arnhem, 17 december 1953 tot 15 maart 1954
boek
Keywords: Frankrijk